Physiological and transcriptional responses to high temperature in arthrospira (Spirulina) platensis C1 - Jaruta Panyakampol (2018)
© The Author 2014. Published by Oxford University Press on behalf of Japanese Society of Plant Physiologists. All rights reserved. Arthrospira (Spirulina) platensis is a well-known commercial cyanobacterium that is used as a food and in feed supplements. In this study, we examined the physiological changes and whole-genome expression in A. platensis C1 exposed to high temperature. We found that photosynthetic activity was significantly decreased after the temperature was shifted from 35 °C to 42 °C for 2 h. A reduction in biomass production and protein content, concomitant with the accumulation of carbohydrate content, was observed after prolonged exposure to high temperatures for 24 h. Moreover, the results of the expression profiling in response to high temperature at the designated time points (8 h) revealed two distinct phases of the responses. The first was the immediate response phase, in which the transcript levels of genes involved in different mechanisms, including genes for heat shock proteins; genes involved in signal transduction and carbon and nitrogen metabolism; and genes encoding inorganic ion transporters for magnesium, nitrite and nitrate, were either transiently induced or repressed by the high temperature. In the second phase, the long-term response phase, both the induction and repression of the expression of genes with important roles in translation and photosynthesis were observed. Taken together, the results of our physiological and transcriptional studies suggest that dynamic changes in the transcriptional profiles of these thermal-responsive genes might play a role in maintaining cell homeostasis under high temperatures, as reflected in the growth and biochemical composition, particularly the protein and carbohydrate content, of A. platensis C1.